ANALISIS KEPUASAN NASABAH ATAS DIMENSI KUALITAS PELAYANAN BANK SYARIAH MANDIRI MALANG - Ikfi Akmalia (Manajemen Bisnis, 2012)
ANALISIS KEPUASAN NASABAH ATAS DIMENSI KUALITASPELAYANAN BANK SYARIAH MANDIRI MALANGIkfi AkmaliaBank MandiriE-mail: lyha_amalya@yahoo.comABSTRACTThe purpose of this study is to know the customers satisfaction of service quality by the Bank SyariahMandiri Malang. A satisfaction index (IKP) and Cartesians Diagram is used to analyze the customersatisfaction of service quality. 16 indicators are used for the IKP, where 9 indicators that representscustomers satisfaction, while 7 indicators dissatisfaction. According to this index, 56% of customersare satisfied, while 43% are not. From the result of calculation above, it can be concluded based onthe Cartesians Diagram that the satisfaction quality dimensions (Tangible, Reliability, Responsiveness,Assurance) in quadrant A, that there needs to be a decrease in service time for queues. For theCartesians diagram in the category C, lower priority is given to accurate recording system free fromerror, employees who gives personal attention to customers, and also a company that truly caresabout the interests of each customers. For Cartesians diagram result in category D is employees whounderstand the specific needs of customers, employees who are always being polite to customers,readiness to respond to customer demand, willingness to help customers, and the use of moderntechnology.Keywords: service quality, customer’s satisfaction